2006
DOI: 10.1021/bi0620959
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Amyloid Fibrils

Abstract: In experiments designed to characterize the basis of amyloid fibril stability through mutational analysis of the Aβ(1-40) molecule, fibrils exhibit consistent, significant structural malleability. In these results, and in other properties, amyloid fibrils appear to more resemble plastic materials generated from synthetic polymers than they do globular proteins. Thus, like synthetic polymers and plastics, amyloid fibrils exhibit both polymorphism, the ability of one polypeptide to form aggregates of different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
104
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 62 publications
11
104
0
6
Order By: Relevance
“…2,[19][20][21] Polymorphism implies different arrangements of b-sheets in amyloid fibrils and therefore differences in the network of hydrogen bonds that determines the structural characteristics and properties of amyloids. 2,22 Previous computational studies have demonstrated that because of differences in the contribution of hydrophobic interaction and hydrogen bonds 16 oligomers with two-fold are more stable than such with the three-fold symmetry.…”
Section: Alred Et Almentioning
confidence: 99%
“…2,[19][20][21] Polymorphism implies different arrangements of b-sheets in amyloid fibrils and therefore differences in the network of hydrogen bonds that determines the structural characteristics and properties of amyloids. 2,22 Previous computational studies have demonstrated that because of differences in the contribution of hydrophobic interaction and hydrogen bonds 16 oligomers with two-fold are more stable than such with the three-fold symmetry.…”
Section: Alred Et Almentioning
confidence: 99%
“…1A). There is significant plasticity in the structural features of amyloid fibrils (8), and alternative models have been proposed (9).…”
Section: A Myloid Fibrils Are Found In the Brain Tissue Of Persons Withmentioning
confidence: 99%
“…These analyses have provided a wealth of information about specific structural details of the peptide in the fibril, for example dihedral torsional angles, protection factors or distances between specific atoms. Atomic models for A␤ peptides and their assembly in different amyloid fibrils have been constructed based on such data (6, 8-10) but these models have not been confirmed by more direct 3D imaging methods.A hallmark of A␤ amyloid fibrils is their substantial polymorphism (11)(12)(13)(14). We have recently shown by transmission electron cryomicroscopy (cryo-EM) and 3D reconstruction that A␤(1-40) fibrils form a range of morphologies with almost continuously altering structural properties (13).…”
mentioning
confidence: 99%
“…A hallmark of A␤ amyloid fibrils is their substantial polymorphism (11)(12)(13)(14). We have recently shown by transmission electron cryomicroscopy (cryo-EM) and 3D reconstruction that A␤(1-40) fibrils form a range of morphologies with almost continuously altering structural properties (13).…”
mentioning
confidence: 99%